And then she fell - Laurens, Stephanie (Laurens, Stephanie. Cynster sisters duo., 2013)
"The only thing more troublesome than a Cynster man is a Cynster lady who believes love is not her destiny. Famously known in London society as the Matchbreaker, Henrietta Cynster has an uncanny skill in preventing ill-fated nuptials, not in falling victim to Cupid's spell. But then she disrupts one match too many, she feels honor bound to help dashing James Glossup find a suitable bride for a marriage-of-convenience--a task infernally complicated by the undeniable, unquenchable attraction that flares between James and Henrietta, who continues to believe she will never fall"--Page 4 of cover.